Testing and numerical modelling of S690 high-strength steel welded I-sections in bending - Chan, Yan Xin (2019)
This paper shows a comprehensive experimental and numerical investigation on the material properties and cross-section bending moment capacities of welded I-sections fabricated from grade S690 high-strength steel plates. Performed on six I-sections welded by gas metal arc (GMA) welding, the experimental study included material tensile coupon tests, residual stress measurements, initial local geometric imperfection measurements, and twelve four-point bending tests. A new predictive model for residual stress patterns within S690 welded I-sections was proposed. Following the experimental study, a finite element numerical study was carried out, where the numerically modelled I-section beams were validated based on the experimentally- derived results, and then employed to perform parametric studies, aiming to generate additional numerical data over a larger range of section sizes. The obtained experimental and finite element moment capacities were used to evaluate the accuracy of the slenderness limits and cross-section resistances from the design provisions listed in Eurocode 3, for S690 high-strength steel welded I-sections in bending. The results of the evaluation revealed that the slenderness limits listed in Eurocode 3 are generally accurate for the cross-section classification of S690 welded I-sections, and the established design cross-section resistances in Eurocode 3 were shown to provide conservative and scattered cross-section resistance predictions for S690 high-strength steel welded I-sections.